Odpowiedzi

2009-10-06T15:19:45+02:00
A) x-2y=4/(-1)
x-2y=-3
-7-2y=-3
-2y=3+7
y=-5

x=-7
y=-5


b)3x+y=-1
4x-3=-2y+4
3x+y=-1/(-2)
4x+2y=7
-6x-2y=2
4x+2y=7
-2x=9
x=-4.5
4*(-4,5)+2y=7
y=12,5


c)2x+2y-x+1=y+2
x+y=1

x+y=1/(-1)
x+y=1
-x-y=-1
x+y=1
x=0
y=0


* to oznacza razy
  • Użytkownik Zadane
2009-10-06T15:28:08+02:00
A)
I x-2y=4
II x+3=2y

z II obliczmy x
x+3 = 2y
x = 2 y - 3
z I obliczmy y
x-2y = 4
( 2y-3) - 2y = 4
0 = 4+3
0 ≠ 7 układ sprzeczny !

b)
3x-1=y-2
4x-3=-2(y-2)

I 3x - 1= y -2
II 4x-3 = -2y + 4

z I obliczmy y
y = -2 -3x +1

z II obliczmy x
4x - 3 = -2 (-2 -3x+1) +4
4x-3= 4 +6x -2 +4
4x -3 = 6x +6
4x- 6x = 6 -3
-2x = 3 / ÷2
x = ⅔

z I obliczmy y

y =-2 - 3 * ⅔ +1
y = -2 -2 +1
y= -3

x= ⅔
y = -3


c)
2(x+y)-(x-1)=y+2
x+y=1


I 2x + 2y -x +1 = y+2
II x+y = 1


z II obliczmy x
x= 1 -y

z I obliczmy y
2x + 2y -x +1 = y+2
2( 1-y) + 2y -(1-y) = y+2
2- 2y + 2y -1 +y = y +2
5y - y = 1
4y = 1 / 4
y = ¼


z II obliczamy x
x= 1 - ¼
x =¾


y= ¼
x=¾